PENGARUH DOSIS PUPUK KANDANG SAPI DAN MACAM PUPUK HAYATI TERHADAP PERTUMBUHAN KEDELAI VARIETAS DEVON I - Daryanti; R. Soelistijono; Endang Suprapti; Achmad Fatchul Aziez; Nendro Asto W (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2020)
The use of chemical fertilizers with high doses and continuously in soybean cultivation can have a negative impact. Efforts to increase soybean production in an environmentally friendly manner need to be done, including using organic fertilizers and biological fertilizers. This study aims to determine the effect of doses of cow manure and kinds of biological fertilizers on the growth of soybean varieties Devon I. The research was conducted in Teguhan Village, Karangmalang District, Sragen Regency, altitude 86 m asl, with soil type Grumosol (PPT Vertisol). This study used a completely randomized block design (RAKL) with two treatment factors, namely the first factor the dose of cow manure consisted of 3 levels, namely P0 = 0 tons/ha, P1 = 10 tons / ha, P2 = 20 tons / ha, and kinds of fertilizers. Biological consists of 4 levels, namely H0 = without biological fertilizers, H1 = Trichoderma, H2 = mycorrhizae, H3 = Trichoderma and mycorrhizae. This study did not use inorganic fertilizers. The results showed that the dose of cow manure had a significant effect on soybean growth, but the type of biological fertilizer and the interaction between the dose of cow manure and the type of biological fertilizer had no significant effect on soybean growth. From the growth achieved, the use of cow manure accompanied by biofertilizer Trichoderma and mycorrhizae has the potential to increase soybean yields.